Peran orang tua terhadap perkembangan bahasa anak tunarungu - Latifah Puti Indani; Ana Rafikayati; Ulfa Dalila; Fika Puji Lestari; Rahayu Nina Sugiarti; Delfi Harlina Natasya Putri (Literal: Disability Studies Journal, 2025)
The language development of deaf children requires a structured approach, early intervention, and support from the family. The subjects in this study are parents of deaf children who experience delayed language development. This study employs a descriptive qualitative approach with a case study design. Data obtained from interviews were analyzed using the Miles and Huberman model. The interview results indicate that parent plays a crucial role in supporting the language development of deaf children. Parents act as companions, facilitators, and also as friends who understand and support one another. Parents hope to their deaf children future is discussed further in this article.